RESISTANCE OF SOYBEAN GENOTYPES TO WHITE MOLD IN DISTINCT AGROECOSYSTEMS - Andrade, Gabriela Carolina Guimarães; Carrer Filho, Renato; Cunha, Marcos Gomes da (REVISTA DE AGRICULTURA NEOTROPICAL, 2018)
White mold (Sclerotinia sclerotiorum) is one of the most important fungal diseases that affect soybean, primarily due to the production of resistant structures called sclerotia. The disease is difficult to control, and sources of genetic resistance are poorly understood. As such, the present study aimed to assess the resistance of soybean genotypes to white mold in two agroecosystems in the Brazil (Barreiras-BA, and Jataí-GO) and analyze the relationship between the disease incidence and the phenotypic characteristics of the genotypes, as well as determine the lodging index, crop cycle and yield. A total of 165 and 33 genotypes were assessed in the regions of Barreiras and Jataí, respectively. To verify the effect of the area, 37 genotypes were planted in both regions. The area effect was assessed for the study variables, and the correlation was significant between the disease and lodging, cycle and production. Considering resistance, area and yield, genotypes ANTA82, 2011L003, 2011L005 exhibited the highest yield and resistance to white mold.